Seasonal Seismicity in the Western Branch of the East African Rift System. Issue 6 (10th March 2020) - Xue, Liang; Johnson, Christopher W.; Fu, Yuning; Bürgmann, Roland
Abstract: Surface load variations from large water bodies alter the state of stress on faults and potentially affect earthquake nucleation processes. We report observational evidence for seasonal variations of seismicity on the border faults of the western branch in the East African Rift System. Relying on water level changes of Lake Victoria and the surrounding rift lakes and soil moisture from the Global Land Data Assimilation System model, we calculate the crustal stress changes using a finite element model. Our results suggest the seasonal hydrological variations produce a 0.2–0.8 kPa Coulomb stress change on the border faults. The primary annual peak in seismicity is coincident with the peak Coulomb stress with an insignificant time lag. The correlation suggests seasonal variations of seismicity rates in the western branch of East African Rift System are modulated by the hydrological loading from Lake Victoria and the large rift lakes in the surrounding region. Plain Language Abstract: Lake Victoria and the surrounding lakes of the East African Rift System (EARS) are the largest lakes (by surface area) in Africa and show annual water level variations concurrent with the regional dry and wet seasons. We use numerical models to calculate crustal stress changes from lake water and soil moisture surface loading and investigate if the hydrological cycle encourages or discourages earthquake activity in the western branch of the EARS. Our results show seasonal hydrological loading produces stress changes at seismogenic depths that have good spatiotemporal correlation with seismicity rate variations in the western branch in the EARS. Hydrological loading from water level changes in Victoria Lake and the rift lakes weakly modulates seismicity rates in the western branch with the most pronounced results in the central Kivu rift and southern Tanganyika rift. Key Points: Seismicity rates in the East Africa Rift System exhibit seasonal variations Hydrological loading from Lake Victoria and rift lakes modulates the stress on the faults of the western branch of East Africa Rift System Hydrological loading Coulomb stress changes correlate with earthquake rate variations in the southern sectors of the western branch